Assessment of Genetic Parameters for Growth, Yield and Morphological Characteristics in Wheat (Triticum aestivum L.) - Ahmad, Ansar; Mishra, Sachchida Nand; Pandey, Mudit; Patel, Rahul Kumar; Yadav, Vikas; Shubham (International Journal of Economic Plants, 2025)
The present study, titled “Assessment of Genetic Parameters for Growth, Yield, and Morphological Characteristics in Wheat (Triticum aestivum L.),” was conducted during the rabi season of 2024–25 at the Agricultural Research Farm, Prof. Rajendra Singh (Rajju Bhaiya) University, Naini, Prayagraj, Uttar Pradesh. This research work had been planned with the objectives to analyze the morphological characters among different wheat genotypes for yield and quality traits, to assess genetic variability, heritability, and genetic advance among wheat, and to estimate the correlation among yield and its component traits. Thirteen wheat genotypes including a check variety, were evaluated under a randomized block design with three replications to assess genetic variability, morphological traits, heritability, and genetic advance. Data were collected for 17 traits. The analysis of variance revealed significant differences among genotypes for all the observed characters. The phenotypic coefficient of variation (PCV) values slightly exceeded the genotypic coefficient of variation (GCV), suggesting minimal environmental influence on trait expression. High estimates of both PCV and GCV were recorded for traits such as grain yield plot-1 (g) and length of peduncle (cm). Traits including number of grains spike-1 and grain yield plot-1 (g) exhibited high heritability coupled with high genetic advance, indicating the predominance of additive gene action. Morphological traits were observed, viz., foliage colour, flag leaf anthocyanin colouration of auricles, ear time of emergence, plant length, ear shape in profile, ear density, grain colour, grain shape, and grain germ width. Among these genotypes, BBW-303 and HD-3086 emerged as superior in terms of yield performance.